Dynamic performance analysis of two regional Nuclear Hybrid Energy Systems. (15th July 2016) - Garcia, Humberto E.; Chen, Jun; Kim, Jong S.; Vilim, Richard B.; Binder, William R.; Bragg Sitton, Shannon M.; Boardman, Richard D.; McKellar, Michael G.; Paredis, Christiaan J.J.
Abstract: In support of more efficient utilization of clean energy generation sources, including renewable and nuclear options, HES (hybrid energy systems) can be designed and operated as FER (flexible energy resources) to meet both electrical and thermal energy needs in the electric grid and industrial sectors. These conceptual systems could effectively and economically be utilized, for example, to manage the increasing levels of dynamic variability and uncertainty introduced by VER (variable energy resources) such as renewable sources (e.g., wind, solar), distributed energy resources, demand response schemes, and modern energy demands (e.g., electric vehicles) with their ever changing usage patterns. HES typically integrate multiple energy inputs (e.g., nuclear and renewable generation) and multiple energy outputs (e.g., electricity, gasoline, fresh water) using complementary energy conversion processes. This paper reports a dynamic analysis of two realistic HES including a nuclear reactor as the main baseload heat generator and to assess the local (e.g., HES owners) and system (e.g., the electric grid) benefits attainable by their application in scenarios with multiple commodity production and high renewable penetration. It is performed for regional cases – not generic examples – based on available resources, existing infrastructure, and markets within the selected regions. This study also briefly addresses the computational capabilities developed to conduct such analyses. Highlights: Hybrids including renewables can operate as dispatchable flexible energy resources. Nuclear energy can address high variability and uncertainty in energy systems. Nuclear hybrids can reliably provide grid services over various time horizons. Nuclear energy can provide operating reserves and grid inertia under high renewables. Nuclear hybrids can greatly reduce GHG emissions and support grid and industry needs.